Transition and worker mobility behaviour of tourism alumni : the case of Switzerland - Heller, Andreas (Array, 2008)
Summary: The research paper investigates the behaviour of tourism alumni at the transition from tourism education market to tourism labour market and from tourism labour market to other labour markets. The paper focuses especially on the decisions of tourism graduates to enter in the tourism labour market as "stayer" or to exit the tourism industry as "mover". The first part commences with some facts and figures from the hotel and restaurant industry of Switzerland regarding the mover issue. The second part discusses the framework of the mover/stayer phenomenon. In the third part, the methodology to determine the transition and worker mobility behaviour and the drivers of this behaviour are presented. A multinomial logit model with a dummy variable controlling for the possibility that tourism alumni may behave differently than alumni of non-tourism sectors was implemented. Descriptive results from a univariate analysis and econometric estimations from a multivariate analysis are described in the fourth part. The influence of gender, age, educa-tion level and other variables are estimated for the tourism industry as well as for non-tourism industries using the example of Switzerland. It will be shown that tourism alumni exhibit higher mover rates and mover probabilities as compared to those of non-tourism industries